Examining gender inequalities in land rights indicators in Asia - Kieran, Caitlin; Sproule, Kathryn; Doss, Cheryl; Quisumbing, Agnes R.; Kim, Sung Mi (Wiley, 2015)
A broad consensus has emerged among both policymakers and researchers that strengthening women's property rights is crucial for reducing poverty and achieving equitable growth. Despite the important role of land in rural livelihoods and as a form of wealth in many Asian countries, surprisingly few nationally representative data exist on women's property rights in Asia.This paucity hinders the formulation and implementation of appropriate policies to reduce gender gaps in land rights. This article reviews the existing micro‐level, large sample data on men's and women's control of land, identifies what can and cannot be measured by these data, and uses these measures to assess the gaps in the land rights of women and men. Utilizing nationally representative individual‐ and plot‐level data from Bangladesh, Tajikistan, Vietnam, and Timor‐Leste, we calculate five indicators: incidence of landownership, distribution of landownership, distribution of plots owned, mean plot size, and distribution of land area, all by sex of owner. The results show large gender gaps in landownership across countries. However, the limited information on joint and individual ownership are among the most critical data gaps and thus are an important area for future data collection and analysis.